2020
DOI: 10.21203/rs.3.rs-87861/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on the Psychological Status of Palestinian Adults in the West Bank, Palestine; A Cross Sectional Study

Abstract: Coronavirus Disease 2019 (COVID-19) caused by a strain of SARS– CoV2. A lot of ministries chose mass lockdown protocol as a way to control the virus spread. One of the lockdown negative consequences is the impact of psychological status which includes a sense of boredom, confusion., psychological stress, anxiety, depression and physical effects. The purpose of this study was to assess and evaluate the effect of COVID-19 pandemic on the psychological status for Palestinian adults, and to establish recommendatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Specifically, people are afraid that they or their family members will become infected or sick [12]. Recent evidence suggests that the fear of COVID-19 infection could elicit anxiety reactions or exacerbate preexisting conditions related to somatic symptoms [13]. Other studies have similarly reported that the fear of becoming infected by COVID-19 could trigger an anxietyrelated disorder [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, people are afraid that they or their family members will become infected or sick [12]. Recent evidence suggests that the fear of COVID-19 infection could elicit anxiety reactions or exacerbate preexisting conditions related to somatic symptoms [13]. Other studies have similarly reported that the fear of becoming infected by COVID-19 could trigger an anxietyrelated disorder [14,15].…”
Section: Introductionmentioning
confidence: 99%